Handling Obstacles to Improving Continuing School Services at Regional High School XI Ministry of Education of West Java Province - Susila, Elis Ela; Saefullah, Selvia Ru’yatus; Adiningsih, Neni Utami; Marlina, Reni; Saadah, Endah (LP. Ma'arif Janggan Magetan, 2024)
This study aims to identify obstacles in assisting school supervisors in an effort to improve the quality of sustainable services. Using a qualitative approach of a case study, data was obtained from ten school supervisors in two Branch Offices of the Education Office through in-depth interviews, observations, and document analysis. The analysis was carried out with the help of Atlas.ti through the stages of open coding, axial coding, and selective coding. The results of the study show that mentoring planning is still dominated by administrative patterns and is not based on data on school needs. Implementation emphasizes document examination rather than reflective dialogue, while monitoring and evaluation are still reporting-oriented. Reflections tend to be sporadic and not well documented. Structural barriers such as uneven superintendent-school ratios, budget constraints, and geographical constraints exacerbate the situation. These findings show a structural-cultural circle that makes mentoring more procedural. The implications of this study confirm the need for data-based mentoring strategies, collective reflection, and strengthening supervisory capacity to get out of administrative traps into transformative roles.